2012
DOI: 10.1002/ece3.360
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure along an altitudinal gradient in Lippia origanoides, a promising aromatic plant species restricted to semiarid areas in northern South America

Abstract: The genetic diversity and population structure of Lippia origanoides, a species of the Verbenaceae family that shows promise as a crop plant, was investigated along an altitudinal gradient in the basin of the Chicamocha River in northeastern Colombia. The economic importance of the species, quality of its essential oils, and the fact that it is restricted to some few semiarid areas in northern South America may put the species at risk in a scenario of uncontrolled harvest of natural populations. Lippia origano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Numerous studies have documented gradients of lower genetic diversity with increased altitude in plants (reviewed in [135], also [136-138]) and animals (reviewed in [139], also [140-142]). While correlations in terrestrial systems are not always negative or linear, they are frequently accompanied by significant differentiation of highland and lowland clades [143-147], and often implicate the greater importance of vertical vs. horizontal distance.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have documented gradients of lower genetic diversity with increased altitude in plants (reviewed in [135], also [136-138]) and animals (reviewed in [139], also [140-142]). While correlations in terrestrial systems are not always negative or linear, they are frequently accompanied by significant differentiation of highland and lowland clades [143-147], and often implicate the greater importance of vertical vs. horizontal distance.…”
Section: Discussionmentioning
confidence: 99%
“…The low genetic diversity observed can be explained by the small population density, which made it impossible to keep sampling with the same distance between the individuals as sampled for Lippia origanoides (Suárez et al, 2008), where the authors reported that the sampling between individuals equidistant 1.2 Km, results in different genotypes. Another factor observed in this study was that the temperature may also have contributed to the genotypic adaptation of the plant (Vega-Vela & Sánchez, 2012;Meira, Martins, & Resende, 2017).…”
Section: Resultsmentioning
confidence: 73%
“…In aromatic species of medicinal interest, studies of genetic structure have concentrated on germplasm of domesticated species or those which chemotypes have already been identified and have consolidated space in the market. Among the species studied are lemon balm (Lippia alba), pepper rosemary (Lippia sidoides) and Mexican oregano (Lippia origanoides Hunth and Lippia graveolens) (Manica-Cattani, Zacaria, Pauletti, Atti-Serafini, & Echeverrigaray, 2009;Vega-Vela & Sánchez, 2012;Rocha et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in populations located at higher altitudes, diversity was significantly lower, probably due to more extreme environmental conditions. Therefore, the differences in altitude between the Chicamocha river basins seem to be relevant in determining the genetic structure of this species [100].…”
Section: Annals Of Reviews and Researchmentioning
confidence: 99%